[Proteomic applications in gynecology-obstetrics]. - De Seta, F; Banco, R; Guaschino, S; De Santo, D; Turrisi, A; Piva, C (Minerva Ginecol, 2011)
Proteomics has recently emerged as a powerful approach both for discovering biomarkers as well as for understanding the physiopathology of unclear gynecological-obstetrical disorders. Currently, several biological fluids and fetal tissues were successfully tested, including maternal plasma, amniotic fluid, cervical-vaginal fluid, urine, saliva, placental trophoblast, amnio-chorionic membranes and cord blood. The potential of proteomics on the polycystic ovary syndrome (PCOS) involves biomarkers discovery for a more accurate diagnosis of the syndrome and identification, within the patients with PCOS, those who respond more easily to treatment and those who will be at increased risk for future metabolic complications. The proteomic approach applied to patients with endometriosis would allow not only a non-invasive early diagnosis, but also a staging of the disease and a prediction of infertility risk. Proteomics also involves oncological field, in order to discover biomarkers that allow early diagnosis and prognosis of female genital malignancies. In addition to this, proteomics could be used to understand and predict obstetrical complications such as recurrent spontaneous abortion, preterm birth and preeclampsia. However, further studies are needed on a larger cohort of patients to introduce these biomarkers in clinical practice.
Keywords: Endometriosis; Female; Genital Diseases, Female; Genital Neoplasms, Female; Humans; Polycystic Ovary Syndrome; Pregnancy; Pregnancy Complications; Proteomics